Noise Exposure in Urban Health Facilities:: An Empirical Study from Khulna - Islam, Md Saiful; Rahman, Md Mizanur (The Jahangirnagar Review, 2025)
Noise pollution is a significant environmental concern, particularly in urban areas where it poses serious risks to public health, well-being, and quality of life. This study assesses the extent of noise pollution in sensitive zones—specifically hospitals and clinics—within the Khulna City Corporation area of Bangladesh. The research aimed to examine spatial and temporal variations in noise levels, identify key noise sources, determine the variation of noise levels with time and evaluate their impacts. Primary data were collected through direct sound level measurements with a digital sound level meter, structured questionnaires, and focus group discussions across selected healthcare facilities. In several locations, average noise levels reached 80 dB, surpassing the recommended indoor limit of 45 dB. Peak noise periods were observed between 10:00–12:00 and 16:00–18:00, primarily due to heavy vehicular traffic and a high influx of visitors. Major sources of noise included road traffic, construction activities, and general crowd movement within hospital premises. Traffic noise was the most significant contributor, with noise levels reaching up to 90 dB near busy roads. The findings reveal that noise levels in and around hospitals frequently exceed the permissible limits set by the Government. Respondents reported adverse effects such as stress, difficulty in sleeping, and reduced concentration. These results highlight the urgent need for targeted noise mitigation strategies and stricter enforcement of environmental noise standards in healthcare settings to protect the well-being of healthcare professionals, patients, and the general public.